Longitudinal Myelitis as a Rare First Symptom of Lupus in Overlap Syndrome - Beata WILCZEK-PARADOWSKA,; Michal PARADOWSKI, (Archives of Rheumatology, 2015)
In this article, we present a 46-year-old female patient who had been diagnosed with Sjögren’s syndrome for 14 years. After initial non-specific signs of abdominal and back pain, neurological symptoms were observed, leading to a final diagnosis of overlap syndrome of neuropsychiatric systemic lupus erythematosus and Sjögren’s syndrome. Inflammatory myelopathy, referred to as longitudinal myelitis, caused severe and persistent neurological deficit in our patient. The provided magnetic resonance imaging scans of the spine show initial and one-year follow-up changes. Thus, we report rare and severe initial symptoms of lupus.